Comparing SociodemographicPredisposing Factors in Major Depressive Disorders (MDD) and Controlsin Kelantan, Malaysia - Mohd Ashari, Noor Suryani; Mohd Yasin, Mohd Azhar; Mohamed Sanusi, Siti Nor Fairus; Shafei, Mohd Nazri (International Journal of Human and Health Sciences (IJHHS), 2019)
Introduction: Major Depressive Disorder (MDD) isexpected to become the second leading cause of worldwide disability by the year 2020 and the major contributor to the overall global burden of disease. Objective: This study was done to compare sociodemographicpredisposingfactors in MDD patients and controls in Kelantan, Malaysia. Methods: A total of 47 MDD patients and 47 healthy controls participated in this study. MDD patients were recruited from Psychiatric Clinic, HUSM and they were diagnosed according to DSM-V criteria. Patients’ biodata, medical and psychiatric history were taken by physician. Data were analysed using Pearson Chi-square and multiple logistic regression. Results: In MDD group, 61.7% were females and 38.3% were males. Forty two percent of MDD were in the age group of 45 to 65 years old and almost 12.8% of MDD patients had family history of depression, while all healthy controls were in good general health and had no family history of depression. Pearson Chi-square revealed that there were significant associations between smoking status (P=0.027), marital status (P=0.007) educational level (P=0.022) and area of living (P=0.0.036) with MDD. The results showed that unmarried person were less likely to have MDD compared to those married with adjusted odds ratio (OR) of 0.31. Smoker were 5.16 at odds of having MDD as compared to non-smoker, while individuals with a low education were more likely to have MDD compared to those highly educated with adjusted OR of 2.04. The result also showed those living in urban area were less likely to have MDD compared to those living in rural area with adjusted OR of 0.48. Conclusion: Higher age, female and positive family history possess a higher tendency of having MDD. In addition, smokers, married, less educated and living in rural area were more likely to have MDD compared to healthy controls. International Journal of Human and Health Sciences Vol. 03 No. 02 April’19. Page: 74-79